1992
DOI: 10.1088/0953-2048/5/4/005
|View full text |Cite
|
Sign up to set email alerts
|

Thin YBCO films prepared by low-temperature spray pyrolysis

Abstract: Thin YECO films were prepared from aerosol by a low-temperature deposition process consisting of two steps-the deposition at atmospheric pressure and firing in vacuum degraded by partial pressure of oxygen-both at temperatures not exceeding 600 "C. A stoichiometric 1-24 aqueous nitrate solution of Y. Ba and Cu constituents was used as a source of aerosol. MgO and AI,O, substrates were heated to 140 to 160°C during deposition. The obtained films were 1 to 10pm thick with T, > 80 K and J, = lo3 to 10' Acm-'. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…above the decomposition temperature of the copper nitrate. We then confirm similar trends that were reported previously [16][17][18][19]21] for YBCO deposition. Such an effect has also been observed for a The temperatures are given by a thermocouple located at the back face of the deposition device.…”
Section: Reactor Designsupporting
confidence: 92%
See 1 more Smart Citation
“…above the decomposition temperature of the copper nitrate. We then confirm similar trends that were reported previously [16][17][18][19]21] for YBCO deposition. Such an effect has also been observed for a The temperatures are given by a thermocouple located at the back face of the deposition device.…”
Section: Reactor Designsupporting
confidence: 92%
“…They emphasize the role of convection in the transport toward the surface where the deposition 'resembles' that of CVD. Later, Jergel et al [17,18] confirmed that high temperature would probably give better results in terms of J c , mostly because a higher surface diffusion enhances sintering and decreases the roughness.…”
Section: Spray Pyrolysis For Ybco Hts Filmsmentioning
confidence: 99%
“…A secondary heat treatment is required to form YBCO and the films generally have rough surfaces with pinholes and cracking. Maximum J c under these conditions are in the range of 10 3 -10 4 A cm −2 [11]. High-temperature spray pyrolysis occurs at temperatures above 500 • C. These films require a copper deficient precursor solution and are smoother and denser [12].…”
Section: Introductionmentioning
confidence: 98%
“…The appearance of the curve is complex because decomposition can take place by more than one step. Further information on nitrate decomposition is given by Jergel et al [13]. The important point to note is that complete decomposition of the present solution, consisting of a mixture of the component nitrates has taken place by 750 • C.…”
Section: Solution Decompositionmentioning
confidence: 72%